(untitled) (Bangladesh Journal of Livestock Research, 2016)
Bangladesh first experienced outbreaks of highly pathogenic avian influenza (HPAI) subtype H5N1 in poultry 2007 and by December 2012 a total of five hundred fifty six (556) outbreaks have been reported of which four hundred ninety nine (499) outbreaks occur in commercial poultry farm as against only fifty seven (57) in backyard poultry chicken. The virus appeared to be a deadly pathogen causing a total of six hundred eight (608) human cases with three hundred fifty nine (359) deaths in the world. In Bangladesh seven (7) human cases have been reported with a singular mortality of a child acquiring the infection from household poultry. There had been six epidemic waves of AI outbreaks in Bangladesh since March 2007 and other new waves seem to have started. From the six years incidence analysis it was found that higher number of outbreaks occurred in the month of February followed by March. The outbreak started from the middle to late winter and continued up to summer. The phylogenetic analysis of viruses isolated till 2010 revealed only one clade 2.2 virus circulating in Bangladesh. But from 2011 two new clades 2.3.2 and 2.3.4 viruses have been introduced. In 2012, it was observed that Clade 2.2 viruses that was in circulation since 2007 were replaced by 2.3.2.1 viruses. Extensive backyard poultry including a large number of ducks, dense human population, and economic dependence of poor people on poultry with low awareness about risk of infection, live bird trading and poor bio-security were critical factors in the spread of avian influenza infection that posses key challenge in rapid containment. Because of the complex situation in poultry production and marketing system, attempts to control this disease through stamping out and bio-security measures have apparently failed in Bangladesh. Bangladesh J. of Livestock Res. 19(1-2): 44-49, Jan-Dec 2012